The Relationship Between Family Support and Medication Adherence Among Tuberculosis (TBC) Patients - Hendar Ristiawan; Hendri Hadiyanto; Hadi Abdillah; Ernawati Hamidah (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Tuberculosis remains a public health problem, and incomplete treatment can adversely affect recovery and community tuberculosis control. Family support may influence medication-taking behavior during therapy and may be related to treatment adherence. Objective: To determine the association between family support and medication adherence among patients receiving tuberculosis treatment in the working area of Cidahu Health Center, Sukabumi Regency. Methods: This quantitative correlational study used a cross-sectional design involving 61 tuberculosis patients selected through purposive sampling. Family support and medication adherence were categorized into low, moderate, and high levels. Because the 3 × 3 contingency table contained sparse and zero cells, the association was analyzed using the Fisher Freeman Halton exact test, with Cramer’s V as the effect-size measure. Results: Family support was significantly associated with medication adherence (p < 0.001; Cramer’s V = 0.47). Among patients with low family support, 79.3% had low adherence, whereas 66.7% of those with high family support demonstrated high adherence. Conclusion: Family support was strongly associated with medication adherence in this sample. However, the cross-sectional design precludes causal inference, and residual confounding from unmeasured clinical, behavioral, and socioeconomic factors should be considered when interpreting the findings.